A law forbidding weapons in certain places, sales of weapons to minors, etc., Ch. 45—Misdemeanors, § 32, in General Ordinances of the City of Brookfield Linn County, Missouri (1900). - (:unkn) unknown (General Publisher, 1900)
If any person shall, within this city, carry concealed upon or about his person, any deadly or dangerous weapon, or shall go into any church or place where people have assembled for religious worship, or into any school room or place where people are assembled for educational, literary or social purposes, or to any election precinct, on any election day, or into any court room during the sitting of court, or into any other public assembly of persons met for any lawful purpose other than military drill, or meeting called under the militia law of this state, having upon or about his person any kind of fire arms, bowie knife, dirk, dagger, sling shot or other deadly weapon, or shall in the presence of one or more persons exhibit any such weapon, in a rude, angry or threatening manner, or shall have or carry any such weapon upon or about his person when intoxicated or under the influence of intoxicating drinks, or shall directly or indirectly, sell or deliver, loan or barter, to any minor any such weapon, without the consent of the parent or guardian of such minor, he shall be deemed guilty of a misdemeanor and upon conviction shall be fined not less than ten nor more than one hundred dollars, or be imprisoned in the city jail not less than five nor more than thirty days."
--
Keywords: CARRY - CONCEALED; TRANSFER - MINORS; BRANDISHING; SENSITIVE PLACES